Design of smart energy level controller for UMP buildings - Nidzamuddeen, Ishak; Abdalla, Ahmed N.; Noraziah, Ahmad; Tan, Chien Sion; Tao, Hai (IEEE, 2011)
Energy efficiency is hot area of research for today researcher. A lot has been done in this regard for managing different types of energy. Management of available resources is one of the basic jobs for researcher for all types of energy. Building energy management that involves efficient equipment system is a hot topic in Malaysian Green technology vision that is costing a lot to the national economy, and its contribution for management is not as it is supposed to be. User comfort, efficient and active control on building energy system is one of the issues needed to be addressed seriously. Following research proposes a smart energy controller system that is specifically designed for campus resources efficient management. The system comprises of wireless control on lighting system that is first focus of the current research.